Community religious expression through sholawat in Bangunrejo Kidul Kedunggalar Ngawi village - Mibtadin Mibtadin; Zainal Habib (Jurnal Ilmu Dakwah, 2022)
Purpose - Islam and Javanese culture can dialogue in harmony, the two are not contradictory. One form of acculturation of the two can be seen from the traditions of rural communities as a form of rural Sufism, namely praising the prophet Mohammad. The people of Bangunrejo Kidul Village still maintain the tradition of praising the prophet as a medium of Islamic symbols. This article looks at how praising the prophet is a form of acculturation between Islam and Javanese culture, the media for da’wa, and the religious expression of rural communities.Method - This research is qualitative descriptive, data collection is done through involved observation, in-depth interviews, and documentation.Result - Praising the prophet is a form of acculturation of Islamic and Javanese culture as seen from the reading of shalawat, dhikr, and prayer accompanied by poetry in Javanese songs while waiting for congregational prayers in the mosque between the call to prayer (adzan) and iqamat. Moral praise is a medium of da’wa aimed at shaping the personality of the community in accordance with Islamic values and upholding the identity of Javanese culture. The value of da’wa in praising the prophet is in the form of perspectives and norms related to aqidah, morals, worship, sharia, and other moral appeals extracted from the Quran and hadith. Praising the prophet is rural Sufism as well as a model for seeking rural spirituality, namely Sufism in low traditions or village traditions as opposed to cosmopolitan traditions. The existence of praising the prophet in society has a dual function, apart from being a religious expression, it is also a safeguard for the existing religious traditions. Praising the prophet becomes a religious education for a cultural inheritance to the next generation as well as for increasing the spirituality and piety of the community. The tradition of praising the prophet is widespread in NU, especially in rural communities, and has become a religious expression to strengthen Nusantara Islam.Implication - The contribution of this article is to strengthen the perspective of the sociology of da’wa in seeing the problem of da’wa in the community, one of which is with local wisdom so that Islam can be accepted.Originality - This study examines sholawat as an acculturation of Islam and culture, media of da'wah, and religious expression of the cultural Islamic community, where the religious behavior of the people of Bangurejo Kidul Village in the context of the sociology of religion where religion is understood as action (religion in action).***Tujuan - Islam dan budaya Jawa dapat berdialog secara harmonis, keduanya tidak bertentangan. Salah satu bentuk akulturasi keduanya dapat dilihat dari tradisi masyarakat pedesaan sebagai bentuk tasawuf pedesaan, yaitu pujian. Masyarakat Desa Bangunrejo Kidul masih mempertahankan tradisi puji-pujian sebagai media syiar Islam. Artikel ini melihat bagaimana pujian merupakan bentuk akulturasi antara Islam dan budaya Jawa, media dakwah, dan ekspresi keagamaan masyarakat pedesaan.Metode - Penelitian ini bersifat deskriptif kualitatif, pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi.Hasil - Pujian merupakan bentuk akulturasi budaya Islam dan budaya Jawa yang terlihat dari pembacaan shalawat, dzikir, dan doa disertai syair dalam bahasa Jawa yang dilantunkan sambil menunggu salat berjamaah di masjid antara adzan dan iqamat. Pujian moral merupakan media dakwah yang bertujuan untuk membentuk kepribadian masyarakat yang sesuai dengan nilai-nilai Islam dan menjunjung tinggi jati diri budaya Jawa. Nilai dakwah dalam pujian berupa cara pandang dan norma yang berkaitan dengan akidah, akhlak, ibadah, syariah, dan himbauan moral lainnya yang bersumber dari Al-Qur'an dan hadits. Pujian adalah tasawuf pedesaan sekaligus model untuk mencari spiritualitas pedesaan, yaitu tasawuf dalam tradisi rendah atau tradisi desa yang bertentangan dengan tradisi kosmopolitan. Eksistensi pujian dalam masyarakat memiliki fungsi ganda, selain sebagai ekspresi keagamaan, juga sebagai pelindung tradisi keagamaan yang ada. Pujian menjadi pendidikan agama untuk pewarisan budaya kepada generasi penerus serta untuk meningkatkan kerohanian dan ketakwaan masyarakat. Tradisi puji-pujian tersebar luas di NU, terutama di masyarakat pedesaan dan telah menjadi ekspresi keagamaan untuk memperkuat Islam Nusantara.Implikasi - Kontribusi artikel ini untuk memperkuat perspektif sosiologi dakwah dalam melihat permasalahan dakwah di masyarakat, salah satunya dengan kearifan lokal agar Islam dapat diterima.Orisinalitas - Kajian ini mengkaji sholawat sebagai akulturasi Islam dan budaya, media dakwah, dan ekspresi keagamaan masyarakat Islam kultural, dimana perilaku keagamaan masyarakat Desa Bangurejo Kidul dalam konteks sosiologi agama dimana agama berada. dipahami sebagai tindakan (religion in action).